STRATEGI SEKOLAH DALAM MENINGKATKAN REPUTASI SEKOLAH FAVORIT DI SMK NEGERI 1 TANJUNG KABUPATEN TABALONG - Miranti Miranti (CV. ADIBA AISHA AMIRA, 2024)
School strategies in improving the reputation of good favorite schools are highly expected to make them reputable and favorite schools. Based on this statement, the formulation of the problem in this study is how is the school strategy in improving the reputation of favorite schools in SMK Negeri 1 Tanjung, Tabalong Regency and what are the driving and inhibiting factors? The objectives to be achieved are to determine the school strategy in improving the reputation of favorite schools in SMK Negeri 1 Tanjung, Tabalong Regency and the driving and inhibiting factors. This type of research is field research and the approach used is a qualitative approach. The object of this study is the school strategy in improving the reputation of favorite schools in SMK Negeri 1 Tanjung, Tabalong Regency. The subjects in this study were the Principal, Vice Principal, Teachers and students of SMK Negeri 1 Tanjung. The data collection techniques were carried out by interview, observation and documentary. Data processing techniques used data reduction, data display and data verification and data analysis used qualitative descriptive. The results of this study indicate that; 1) School strategy in order to improve the reputation of favorite schools in SMK Negeri 1 Tanjung, Tabalong Regency by formulating strategies, planning strategies to be implemented in the future, implementing the strategy and finally evaluating it. 2) Driving and inhibiting factors. Driving factors are in the form of large funds obtained from BOS, and cooperation from all parties. Inhibiting factors in improving the reputation of SMKN 1 Tanjung are not so significant, because they are only constrained by the time it is achieved or unexpected, for example changing schedules, uncertain natural conditions, sick students, or the condition of accompanying teachers who suddenly get sick, and other small things and all of that has been anticipated or overcome well.